Cadmium quantification in Brazilian mothers colostrum: a regional study Quantificação de cádmio em colostro de mães brasileiras: um estudo regional - Luiz Fernando C. Nascimento; Hélcio José Izário Filho; Mariana Luz Pereira; Nivaldo Baccan (Instituto Materno Infantil de Pernambuco, 2005)
OBJECTIVES: to estimate the amount of cadmium in human colostrum of mothers from Taubaté. METHODS: it was a cross-sectional study with mothers who delivered in University Hospital of Taubaté, in year 2003. The colostrum was collected in special tubes, one day after the delivery and frozen at -200 C. The independent variables were maternal age, birthweight, gestational age, parity, dietary habits, smoking report and maternal occupation. Cadmium was quantified by atomic absorption spectrometry. It was used Mann-Whitney non-parametric approach to compare mean values; Pearson correlation was also used to verify associations. The level of significance was alpha = 5%. RESULTS: the mean value of cadmium was 54.5 mg/L (sd=381.0 mg/L). Cadmium was detected in 18 out of 58 samples (31.0%). There was neither correlation nor differences between the cadmium values and the independent variables maternal age, birthweight, gestational age, parify and smoking report. CONCLUSIONS: these values are above those the amounts described in other papers and it is important to identify the possible sources of this heavy metal in maternal environment. OBJETIVOS: estimar a quantidade de cádmio em colostro de mães de Taubaté. MÉTODOS: foi realizado um estudo do tipo transversal envolvendo mães que deram à luz no Hospital Universitário de Taubaté, no ano de 2003. O colostro foi coletado até um dia após o parto, em tubos de polipropileno previamente tratados e refrigerado a -20° C. As variáveis independentes foram idade materna, peso do recém-nascido, idade gestacional, paridade, hábitos alimentares, relato de fumo e ocupação materna. Cádmio foi quantificado através da técnica da espectroscopia de absorção atômica. Foram utilizados a técnica não-paramétrica de Mann-Whitney para comparação das médias e a correlação de Pearson para verificar associações. O nível de significância adotado foi alfa = 5%. RESULTADOS: o valor médio de cádmio encontrado foi 54,5 mg/L (dp = 381,0 mg/L), sendo quantificado em 18 de 58 amostras (31,0%). Não foram observadas correlações nem diferenças entre o conteúdo de cádmio e as variáveis estudadas. CONCLUSÕES: os valores encontrados neste estudo estão acima dos encontrados por outros autores e é importante identificar as possíveis fontes deste contaminante no ambiente materno.